Ecological Landscape and Endemic Diseases of the Kerinci Community Before the Construction of the Kerinci Highway 1903-1915 - Ilma Ilma (UIN Imam Bonjol Padang, 2025)
Before the construction of the Kerinci highway (Korintjiweg) from 1903 to 1915, the Kerinci region was in a state of extreme isolation due to the difficulty of accessing and leaving the area. This condition limited the mobility of the residents, economic activities were conducted simply, and the health patterns of the community were greatly influenced by the humid mountainous environment and the distance from health service centers. This research aims to describe the health conditions of the Kerinci community before the existence of the highway by examining the types of diseases that emerged, environmental factors affecting health, and how isolation shaped disease patterns that tended to remain constant over time. This research uses historical methods through source collection, document reliability examination, interpretation, and the compilation of analysis results based on health reports from the Dutch colonial government and administrative records. The research results show that the isolation of Kerinci provided protection from several dangerous diseases commonly found in coastal areas, such as cholera, smallpox, and syphilis. However, the community still faces diseases that arise from daily life, such as skin diseases, respiratory issues, digestive problems, and fatigue due to heavy agricultural work. Some reports also noted the presence of early cases of gonorrhoea and leprosy, indicating limited connections with other regions although it has not yet caused widespread outbreaks. The absence of permanent healthcare facilities and reliance on traditional medicine make the community vulnerable to chronic diseases or more severe infections. Overall, this study shows that the health conditions of the Kerinci community before the construction of the highway were shaped by the isolated nature of the region, the daily lives of the community relying on nature, and the lack of healthcare services, resulting in a stable disease pattern but with clear vulnerabilities.